2013
DOI: 10.1111/bju.12348
|View full text |Cite
|
Sign up to set email alerts
|

Electrocautery‐induced cavernous nerve injury in rats that mimics radical prostatectomy in humans

Abstract: Objective• To investigate the early and delayed effects of cavernous nerve electrocautery injury (CNEI) in a rat model, with the expectation that this model could be used to test rehabilitation therapies for erectile dysfunction (ED) after radical prostatectomy (RP). Materials and Methods• In all, 30 male Sprague-Dawley rats were randomly divided equally into two groups (15 per group). The control group received CNs exposure surgery only and the experimental group received bilateral CNEI.• At 1, 4 and 16 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Both our study and Cellek’s study [ 35 ] found that stimulation of the MPG would cause contraction of the bladder, pelvic floor and rectum. This would result in an inaccurate measurement of CN-mediated neurotransmissions, as the CN is the main innervation responsible for the erection [ 36 ]. (4) In the method of cannulation into the shaft of the penis, the cannulating needle should enter the penile shaft at about a 10-degree angle.…”
Section: Discussionmentioning
confidence: 99%
“…Both our study and Cellek’s study [ 35 ] found that stimulation of the MPG would cause contraction of the bladder, pelvic floor and rectum. This would result in an inaccurate measurement of CN-mediated neurotransmissions, as the CN is the main innervation responsible for the erection [ 36 ]. (4) In the method of cannulation into the shaft of the penis, the cannulating needle should enter the penile shaft at about a 10-degree angle.…”
Section: Discussionmentioning
confidence: 99%
“…Although most experimental animal models of CN injury are mechanically created trauma models such as “crush,” “freezing,” and ligation, 18 thermal damage also could be a potential cause of ED. 19 We applied electrical coagulation to the bilateral CNs for 0.5 second at 50 kHz and 16 W using a bipolar forceps. This condition provided a stable platform to study the therapeutic effects of infused bone marrow–derived MSCs after CN injury.…”
Section: Discussionmentioning
confidence: 99%
“…Using this model, the consequences of the deafferentation of autonomic pelvic ganglia on their neurochemistry and nerve regeneration (Calenda et al 2012; Girard et al 2013; Keast 2006; Song et al 2014), on erectile dysfunction (Calenda et al 2012; Karakiewicz et al 1996; Song et al 2014; Yamashita et al 2009) or bladder and urethral functions (Lee et al 2013) have been examined. Axotomy of the pelvic nerve or its tributaries [lumbar 6 (L6) and sacral 1 (S1) spinal nerves axotomy] was introduced for the study of the neural and behavioral effects of vaginocervical stimulation (Pfaus et al 2006), neurochemical changes in the lumbar sympathetic chain (LSC) (see Brumovsky et al 2011b), changes in colonic transit (Ridolfi et al 2011), or the physiology of parturition (Martinez-Gomez et al 1998; Tovar et al 2013).…”
Section: Introductionmentioning
confidence: 99%